Cyberbullying, estratégias de coping e esquemas iniciais desadaptativos em adolescentes - Mallmann, Caroline Louise (2016)
Cyberbullying is defined as a phenomenon involving aggressive, intentional and repetitive behaviors, carried out by electronic means, during a given period and perpetrated by an individual or group against a victim with difficulties in defending herself or himself. Coping strategies are a set of mutable cognitive and behavioristic efforts, used to deal with internal or external demands that are evaluated by the individual as excessive to his or her resources. Finally, Early Maladaptive Schemes (EMSs) are a dysfunctional cognitive and emotional pattern, related to oneself or to other individuals, developed during childhood or adolescence. Thus, the objective of this paper was to investigate the process of cyberbullying in adolescents of two cities in the State of Rio Grande do Sul (Brazil), as well the relation of this phenomenon with coping strategies and with Early Maladaptive Schemes. To do so, the investigation was divided into two empirical articles. The first article aimed at relating the social roles in cyberbullying (non-involved, victims, aggressors or victim-aggressors) and the styles of coping. A total of 273 students took part in the survey (average age=14,91; DP=1.43). The teenagers were invited to answer the Sociodemographic Data Questionnaire, the Revised Cyberbullying Inventory (RCBI), the Young Schema Questionnaire for Adolescents (SQA) and the Lazarus and Folkman Coping Strategies Inventory. The results indicated that almost 58% of the adolescents suffered or perpetrated some sort of virtual violence. Moreover, the average of the coping strategies of self-control, social support and escape-avoidance were significantly higher to the victims than to the non-involved. On the other hand, the confrontation strategy was more frequent in the reports of victim-aggressors than in the non-involved. It is discussed the high cyberbullying frequency in the sample surveyed, as well as the dominance of coping strategies focused on emotion. The second article aimed at investigating the relations between social roles in cyberbullying and the Early Maladaptive Schemes proposed by Young. The participants, as well as the procedures, were the same as in Study 1. The results showed that girls tend to be more involved in cyberbullying practices than boys. Adolescents involved in cyberbullying as victims and victim-aggressors tend to present higher averages in the majority of EMSs than the non-involved. Victims presented significantly higher scores in the Defect scheme in comparison to aggressors, victim-aggressors and non-involved, as well as presented significantly higher scores in the Distrust, insufficient Self-Control, Subjugation and Self-Sacrifice Schemes in comparison with the non-involved and in the Entanglement Scheme in comparison to victim-aggressors. On the other hand, the victim-aggressors presented higher scores in the grandiosity, insufficient self-control and search for approval schemes. It was observed a higher frequency of cyberbullying among girls, which brings interpretations on cultural and biological influences related to genre and aggressiveness. Finally, it is equally debated the issue of EMSs as possible factors that make the individual vulnerable to the cyber victimization or that allow the perpetration of aggressive acts in the virtual context.